Judiciary involvement in authoritarian repression and transitional justice: the Spanish case in comparative perspective - Aguilar Fernández, Paloma (International journal of transitional justice, 2013)
Why have some democracies made considerable progress in prosecuting dictatorship-era human rights violations or in publicly exposing the truth about repression while others still have amnesty laws that prevent, or at least hinder, even the judicial review of such abuses? This article compares Spain, Chile and Argentina to understand the impact of their contrasting histories of repression on how they have dealt with their violent pasts. I assess whether a greater degree of legal repression and direct judicial involvement in repression explains why there is more resistance to prosecuting those responsible for human rights violations, establishing truth commissions or annulling the political sentences of the past during democratization. Once democracy has been consolidated, different dynamics may emerge, but this history of judicial complicity has proved to be a key factor in understanding the continuous lack of judicial accountability in Spain.